Clinical anemia predicts dermal parasitism and reservoir infectiousness during progressive visceral leishmaniosis. - Max C Waugh; Karen I Cyndari; Tom J Lynch; Soomin Koh; Ferney Henao-Ceballos; Jacob J Oleson; Paul M Kaye; Christine A Petersen (Public Library of Science (PLoS), 2024)
Dogs represent the primary reservoir for Leishmania infantum human visceral leishmaniasis (VL) transmitted through phlebotomine sand flies. Public health initiatives targeting zoonotic VL commonly focus on dogs with severe clinical disease, often in renal failure, as they have previously been considered the most infectious to sand flies. However, more recent studies suggest that dogs with mild to moderate clinical disease may be more infectious than dogs with severe disease. The mechanisms of infectiousness from the skin and how this relates to transmissibility as clinical disease progresses is largely unknown. We evaluated dermal parasitism in dogs naturally infected with L. infantum across the four LeishVet clinical stages of disease. We establish the relationship between dermal parasitism, critical, frequently observed, clinical parameters such as anemia and creatinine, and infectiousness. Using RNAscope and confocal microscopy, we found notable variation in dermal parasitism between dogs, particularly within LeishVet II. Dogs with mild disease had significantly less dermal inflammation and parasitism than dogs with moderate or severe disease. We found significant correlations between anemia, dermal parasitism, and infectiousness (p = 0.0098, r = -0.4798; p = 0.0022, r = -0.8364). In contrast, we did not observe significant correlation between creatinine, a measure of renal function, and dermal parasitism or infectiousness. Host blood cell abnormalities, including anemia, correlate with infectiousness to sand flies. As these signs of disease often appear earlier in the course of disease, this indicates that classical measures of disease severity do not necessarily correlate with infectiousness or epidemiological importance. Public health initiatives attempting to break the zoonotic cycle of L. infantum infection should therefore focus on preventing transmission from infectious, anemic dogs, and not those with the most severe disease.